Senam Pagi Sebagai Upaya Meningkatkan Kebugaran dan Interaksi Sosial Masyarakat Desa Asrikaton Kabupaten Malang - Yulianti, Eny; Fitriyah, Ulil; Ro’iyah, Maulidhotur; Fadlan, Mochamad Lailul; Haq, Naufal Rizqi; Majdi, Dani Sanaya; Al-Rosyid, Ahmad Taufiqurrahman; Az Zahra, Audy; Widad Hakim, Sofwatul; Zamroni, Anits (Jurnal Surya, 2023)
Morning exercise is a physical activity that has long been known to have positive benefits for individual health. This study aims to investigate the effects of a morning exercise program on the fitness and social interaction of the community in Asrikaton Village, Malang Regency, Indonesia. The study actively involved the participation of villagers of various age groups. The morning exercise program was conducted regularly every day and assisted by experienced instructors in the field. During the research period, health and familial data were collected through surveys, observations, and interviews with morning exercise participants. Observations by the KKM group from UIN Maulana Malik Ibrahim Malang showed that the majority of morning exercise participants were aged 25-39 years, and most residents of Asrikaton Village exercised only once a week. The morning exercise program had a significant positive impact on the physical and mental health of the Asrikaton Village community. There was a notable increase in physical fitness, a decrease in stress levels, and an improvement in the sense of togetherness, social interaction, and family relationships. Participation in morning exercise also contributed to raising awareness of the importance of a healthy lifestyle. Therefore, morning exercise serves not only as an effort to improve public health but also helps strengthen family ties through social interaction within the Asrikaton Village community. This research provides a strong foundation to support and encourage morning exercise activities in rural communities as part of broader health and community-building efforts.,